2019
DOI: 10.7150/jca.31202
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of surgery in the multimodality treatment of stage IIB-IIIC small cell lung cancer

Abstract: Surgery combined with chemotherapy/radiotherapy is recommended for early stage small cell lung cancer (SCLC); however, the role of surgery in the multimodality treatment of advanced disease remains controversial. The clinical data of patients between 2000 and 2015 were obtained from the Surveillance, Epidemiology, and End Results database. The surgery group included 998 patients with stage IIB-IIIC. A matched non-surgery group (n = 2994) was generated by propensity score matching. The Kaplan-Meier method and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…In patients with lymph node metastasis, concurrent chemoradiation is the cornerstone of treatment. Although some retrospective studies found that surgery combined with chemoradiation can enhance survival in stage II/III SCLC [ 5 , 11 14 ], this has not been demonstrated in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with lymph node metastasis, concurrent chemoradiation is the cornerstone of treatment. Although some retrospective studies found that surgery combined with chemoradiation can enhance survival in stage II/III SCLC [ 5 , 11 14 ], this has not been demonstrated in clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…At present, video-assisted thoracoscopic surgical treatment is a main choice [5][6][7]. In the past two years, robot-assisted pneumonectomy has gradually been carried out clinically [8]. However, less than 40% of patients are still diagnosed when the lesion is confined to the lungs, which is still a problem for patients [9].…”
Section: Introductionmentioning
confidence: 99%
“… 6 Surgical treatment is therefore rarely possible, but in the last few years it has been recommended for certain patients with early-stage disease. 7 Before the introduction of platinum-based antineoplastic drugs for the treatment of malignant disease, the median survival of patients diagnosed with small cell lung cancer was two to three months. 8 , 9 The survival rate has increased four to five times with chemotherapy, but for most patients with extensive-stage disease it does not exceed ten months.…”
Section: Introductionmentioning
confidence: 99%